1992
DOI: 10.1159/000150235
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Adenovirus Genome Type 7h: Analysis of Its Relationship to Other Members of Serotype 7

Abstract: Ad7h is a newly identified genome type associated with severe lower acute respiratory infections and has so far been isolated only in South America. To obtain a clue to its possible origin, the degree of restriction enzyme site homology between adenovirus genome type 7h and those representative of the three described genomic clusters (GC) for serotype 7 was studied by analysis of pairwise comigrating DNA restriction fragments (PCRF) after digestion with BamHI, BglI, BglII, BstEll, EcoRl, Hindlll, Hpal, SalI, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…All U.S. (and eastern Ontario, Canada) Ad7d2 isolates and an Ad7d2 reference strain from Israel ( 37 ) gave identical restriction patterns for Bam HI, BcI I, Bgl I, Bgl II, Bst EII , Eco RI, Hpa I, Hin dIII, Sal I, Sma I, Xba I, and Xho I. Identical restriction profiles were also obtained with four U.S. Ad7h isolates and a 1998 isolate of Ad7h from Chile, which were similar to profiles described for Ad7h strains isolated in Argentina and Chile (formerly designated Ad3f) ( 41 , 42 , 44 ). …”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…All U.S. (and eastern Ontario, Canada) Ad7d2 isolates and an Ad7d2 reference strain from Israel ( 37 ) gave identical restriction patterns for Bam HI, BcI I, Bgl I, Bgl II, Bst EII , Eco RI, Hpa I, Hin dIII, Sal I, Sma I, Xba I, and Xho I. Identical restriction profiles were also obtained with four U.S. Ad7h isolates and a 1998 isolate of Ad7h from Chile, which were similar to profiles described for Ad7h strains isolated in Argentina and Chile (formerly designated Ad3f) ( 41 , 42 , 44 ). …”
Section: Resultssupporting
confidence: 62%
“…Cases of severe pneumonia and neurologic disease were reported from a recent regional epidemic of Ad7d2 in Japan ( 15 ), but there was no evidence that these severe cases were more common than those reported for outbreaks involving other Ad7 genome types. Ad7h, a genetically unique recombinant between Ad7 and Ad3 ( 42 ), has been linked to increased illness and death in infants in Chile and Argentina, where it is second only to Human respiratory syncytial virus as a cause of severe viral pneumonia in infants and young children ( 34 , 52 ). However, in this study, too few cases of Ad7h infection were identified to assess differences in disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, epidemiological studies indicate that the global prevalence patterns of HAdV genome types do shift over time and geographical region (10,18,27,28). This, along with the genome data presented here, suggests that it is advisable and prudent to design HAdV vaccines from strains that offer the greatest protection against the prevalent genome type and to continue surveillance and vaccine redevelopment with periodic evaluations of current field strains.…”
Section: Vol 43 2005 Genomes Of Two Adenovirus Vaccines 3089mentioning
confidence: 74%
“…This same genotype was found to become prevalent in Chile during 1986 (Kayon & Suarez 1990). Later, Niel et al (1991) ognized (Kayon & Wadell 1992) as the same virus and belonging to serotype 7, genetic type 7h.…”
mentioning
confidence: 74%